2019
DOI: 10.3390/en12020321
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Strategies for Lowering the Operation Temperature in Existing District Heating Networks

Abstract: District heating systems have an important role in increasing the efficiency of the heating and cooling sector, especially when coupled to combined heat and power plants. However, in the transition towards decarbonization, current systems show some challenges for the integration of Renewable Energy Sources and Waste Heat. In particular, a crucial aspect is represented by the operating temperatures of the network. This paper analyzes two different approaches for the decrease of operation temperatures of existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 20 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…[1] showed that the construction of a network in urban areas causes a significant reduction of carbon dioxide emissions to the air, while Ravina et al [2] pointed out that district heating networks could contribute to the reduction of emissions of nitrogen oxides and suspended particulates in the Italian city of Turin. The ecological effect may be raised by the cooperation of district heating networks pre-insulated especially by low-temperature heating networks with renewable heat sources [3,4]. The work of district heating networks is undoubtedly influenced by the management of district heating networks [5][6][7], as well as the type of local heat consumers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[1] showed that the construction of a network in urban areas causes a significant reduction of carbon dioxide emissions to the air, while Ravina et al [2] pointed out that district heating networks could contribute to the reduction of emissions of nitrogen oxides and suspended particulates in the Italian city of Turin. The ecological effect may be raised by the cooperation of district heating networks pre-insulated especially by low-temperature heating networks with renewable heat sources [3,4]. The work of district heating networks is undoubtedly influenced by the management of district heating networks [5][6][7], as well as the type of local heat consumers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained with the DH network were (i) energy savings higher than 21% for 33% of the campus buildings, (ii) increase in consumption of 20% in 17% of the buildings, and (iii) no significant differences in the remaining buildings. Neirotti et al [20] studied two different approaches for decreasing the DH operating temperatures, starting from a different control strategy involving night-time operation to avoid the morning peak demand, and the partial insulation of the buildings to decrease the operating temperatures without modifying the heating system of the end-users. In the first approach, it was possible to decrease the network temperature down to 50-60 • C without compromising the comfort and the end-users' energy consumption increased by 3.5% with respect to the reference case due to the continuous operation of the heating system, although the network losses decreased.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the user system is separated from DH network by a heat exchanger (indirect connection), the actual radiator supply temperature strongly depends on the type of control and on the characteristics of the heat exchanger. Neirotti et al [31] explore the effect of reducing DH temperature on a typical North-Italian building with radiator-based heating, comparing two different refurbishing strategies based on continuous operation and on building insulation improvement. They assume a coil heat exchanger modeled by means of a Modelica library component, although DH substations more often use plate heat exchangers.…”
Section: Introductionmentioning
confidence: 99%